The PROMISE-V2 PRIMARY score and SULmax [18F]PSMA-1007 PET/CT in primary staging of prostate cancer - J. Antonio Serna-Macias; M. Lourdes Garcia-Colmenero; Emilly A. Cortes-Mancera; E. David Muñoz-Carpio; Mixel Z. Baltierra-Hernandez (Journal of the Mexican Federation of Radiology and Imaging)
Introduction: The PRIMARY score of the PROMISE-V2 criteria for primary staging of prostate cancer (PCa) and its relationship with the maximum standardized uptake value normalized to lean body mass (SULmax) have not been evaluated. This study determined the relationship between the SULmax value in [18F]PSMA-1007 PET/CT and the PROMISE-V2 PRIMARY score in patients with untreated PCa in primary staging. Material and Methods: This cross-sectional study included patients with PCa in primary staging. The SULmax value [18F]PSMA-1007 PET/CT of the intraprostatic lesion was recorded, and the PRIMARY score was assessed based on the pattern of affected prostate zones (peripheral, transitional, or central) and the distribution of prostate-specific membrane antigen (PSMA) uptake (focal or diffuse). Lymph node (pelvic or extrapelvic) spread and metastasis (bone, lung, and/ or brain) were determined. Results: Fifty-five patients with PCa at primary staging were included. The SULmax value of an intraprostatic tumor in PRIMARY score 2 was 5.15 ± 0.54 g/mL; in PRIMARY score 3, 7.11 g/mL; in PRIMARY score 4, 8.31 ± 1.92 g/mL, and in PRIMARY score 5, 22.64 ± 7.77 (p < 0.001). The SULmax value of [18F]PSMA increased in direct association with the PRIMARY score in cases with an intraprostatic tumor (11.49 ± 6.69 g/mL (p < 0.001) and an intraprostatic tumor + pelvic lymph nodes (15.17 ± 9.72 g/mL). In contrast, cases with extrapelvic lymph nodes or metastases (bone, brain, or lung) had lower SULmax values (12.43 ± 8.73 g/mL) (p < 0.001). Conclusion: Our study showed an association between the SULmax value and the PRIMARY score according to the affected anatomical zone, the expression patterns and a SULmax > 12 g/mL. The expression of PSMA uptake in the local tumor was highest in the pattern of focal involvement in the peripheral zone (PZ) as long as the disease was confined to the pelvis.